Automatic land subsidence monitoring system based on weak-reflection fiber gratings - Jianhui HE; Jincai ZHANG; Yong CHEN; Xingguang YAN; Bin SHI; Guangqing WEI; Lixiang JIA; Suping LIU (Shuiwen dizhi gongcheng dizhi, 2021)
Fiber optic sensing technique has the features of distributed and high-precision measurement, especially in land subsidence monitoring. Due to the high cost and complicated environment, the monitoring data is mostly collected manually and it limits the real-time acquisition of land subsidence performance under special circumstances. Based on full-section monitoring of land subsidence in boreholes using the distributed fiber optic sensing (DFOS) technique, the automatic land subsidence monitoring system based on weak-reflection fiber gratings is proposed and established in Hengshui, China. The system utilizes the techniques of weak-reflection fiber gratings, time division multiplexing, Internet of Things, database, and 4G network, then realizes automatic monitoring of land subsidence and real-time remote data collection. Through the client system software to realize the data storage, query, and analysis. The monitoring results show that the compressive deformation of the soil occurs at aquitards (Ad2, Ad3, Ad4). For the aquifers which composed of sand soil (100～400 m depth), there is a fluctuating change which influenced by seasonal extraction of the groundwater. Consequently, a slight rebound occurs in winter and then compresses in spring. The feasibility and accuracy of the system have been verified in the field investigation, and the system makes the process of monitoring more automatic, standard, and cost-effective.